1419. Matters of the Heart: A Scoping Review Toward Better Management‌ ‌of‌ Nontuberculous‌ ‌Mycobacterial‌ ‌Infections of‌ Cardiac ‌Devices‌. (15th December 2022) - Mahatanan, Rattanaporn; Ovalle, Anais; Lee, Devin; Alkozah, Maria; Talbot, Elizabeth
Abstract: Background: Medical device infections caused by nontuberculous mycobacteria (NTM) are increasingly reported in the literature. Management is complex and often guided by expert opinion, in the absence of evidence-based guidelines. Methods: We searched available databases for reports of‌ implantable‌ cardiac device-related‌ (ICDR) infections with NTM. We collected patient-level characteristics, microbiological, and treatment data, and used univariate analysis to correlate with reported outcome, which we defined as death, treatment failure, relapse after treatment completion, cure, and treatment completion. Results: Of 2573 potential eligible articles, 68 articles were included, representing 112 patients. The average patient age was 61 years, and 6% of patients were immunocompromised. Of 12 species reported, 65% were rapid growers, with M. fortuitum most common. Prosthetic heart valves and pacemaker/automatic implantable cardiac devices (AICD) were the most commonly reported infected devices (45% and 37%, respectively). Diagnosis was often delayed, and confirmed with culture (62%, 41% blood cultures) and 16s ribosomal RNA gene sequencing data (14%) of cases. Antimicrobial susceptibility was available in 55% of cases. 70% of patients received > 2 antibiotics and, of these, 41% included a macrolide. Devices were removed for 65% of patients, more commonly if the infected deice was a pacemaker or AICD than another type of cardiac device (86% vs 56%, p=0.02). 67% of patients with prosthetic valves underwent valve replacement. Compared with those who did not have their device removed, patients who underwent device removal were less likely to die (23% vs 48%, p=0.02) and more likely to have favorable outcomes (68% vs 28%, p=0.002). Conclusion: Reports of ICRD NTM infections were common, and suspicion should be high even for those without immunocompromising condition. Determining outcome was challenging and should be standardized to provide an evidence base for better management. In our analysis, patients who underwent device removal had improved survival, suggesting either that comorbidity precluded device removal and/or that removal may be an essential part of the management. Disclosures: All Authors : No reported disclosures.